2010
DOI: 10.1586/eci.10.19
|View full text |Cite
|
Sign up to set email alerts
|

Summary of the International Multicenter Prospective Angioedema C1-inhibitor Trials 1 and 2 (IMPACT1 and 2)

Abstract: Hereditary angioedema (HAE) is an autosomal dominant disease characterized by deficiency of C1 inhibitor (C1-INH) that commonly presents with recurrent swelling affecting different parts of the body. Supplementation with C1-INH is successfully used to treat HAE in selected countries, mostly in Europe. Berinert P (CSL Behring, Marburg, Germany), a human plasma-derived C1-INH, was studied in the International Multicenter Prospective Angioedema C1-inhibitor Trial 1 (IMPACT1) that was completed in 2007. It was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
3
8
0
Order By: Relevance
“…A recent placebo‐controlled study in patients with Type I or II HAE confirmed that pC1‐INH administered at a weight‐based dose of 20 U/kg induced initial symptom relief from acute abdominal and facial attacks within a median of 30 minutes 14 . In addition, an open‐label extension to this study showed that the 20 U/kg dose of pC1‐INH also induced initial symptom relief from acute peripheral attacks within a median of 30 minutes 15 . The same extension study showed that life‐threatening laryngeal attacks are especially well controlled by this dose of pC1‐INH, with initial symptom relief within a median of 15 minutes 16 …”
supporting
confidence: 61%
See 1 more Smart Citation
“…A recent placebo‐controlled study in patients with Type I or II HAE confirmed that pC1‐INH administered at a weight‐based dose of 20 U/kg induced initial symptom relief from acute abdominal and facial attacks within a median of 30 minutes 14 . In addition, an open‐label extension to this study showed that the 20 U/kg dose of pC1‐INH also induced initial symptom relief from acute peripheral attacks within a median of 30 minutes 15 . The same extension study showed that life‐threatening laryngeal attacks are especially well controlled by this dose of pC1‐INH, with initial symptom relief within a median of 15 minutes 16 …”
supporting
confidence: 61%
“…14 In addition, an open-label extension to this study showed that the 20 U/kg dose of pC1-INH also induced initial symptom relief from acute peripheral attacks within a median of 30 minutes. 15 The same extension study showed that life-threatening laryngeal attacks are especially well controlled by this dose of pC1-INH, with initial symptom relief within a median of 15 minutes. 16 A practical limitation of C1-INH replacement therapy is the need for intravenous (IV) administration, which usually involves patients having to travel to a suitable clinic or local physician for treatment.…”
mentioning
confidence: 81%
“…In addition to ecallantide, which is approved for the treatment of acute HAE attacks affecting all anatomic locations in patients aged 16 years and older, Berinert P, an intravenously administered, human plasma-derived C1-INH concentrate, has been approved for acute abdominal and facial attacks [16,17,35]. Additionally, icatibant, a subcutaneously administered bradykinin B2 receptor antagonist, is approved for the treatment of acute attacks of HAE in patients aged 18 years and older [20,21].…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%
“…The availability of multiple treatment options will greatly enhance the quality of care for HAE patients. The development of updated Stolz & Sheffer (36) 28 (35) Most common TEAEs, n (%) …”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%
“…It can also be taken as individual replacement therapy (IRT); meaning that the patient takes the drug as soon they think they are going to have an attack (83). The dosage differs between the two main products: Berinert is dosed at 20 IU/kg bodyweight and Cinryze is dosed at 1000 IU irrespective of bodyweight (84,85). The dosage of rhC1INH conestat alfa is 50 IU/kg bodyweight up to a weight of 84 kg, after which the dose is 4200 IU, and conestat alfa, extracted from the breast milk of transgenic rabbits that express human rhC1INH, is also given intravenously (86,87).…”
Section: Treatmentmentioning
confidence: 99%